Solution pH jump during antibody and Fc-fusion protein thaw leads to increased aggregation - Kevin P. Kent; Chad E. Schroeder; Chandana Sharma (Elsevier, 2018)
Freeze-thaw cycles impact the amount of aggregation observed in antibodies and Fc-fusion proteins. Various formulation strategies are used to mitigate the amount of aggregation that occurs upon putting a protein solution through a freeze-thaw cycle. Additionally, low pH solutions cause native antibodies to unfold, which are prone to aggregate upon pH neutralization. There is great interest in the mechanism that causes therapeutic proteins to aggregate since aggregate species can cause unwanted immunogenicity in patients. Herein, an increase in aggregation is reported when the pH is adjusted from pH 3 up to a pH ranging from pH 4 to pH 7 during the thaw process of a frozen antibody solution. Raising the pH during the thaw process caused a significant increase in the percent aggregation observed. Two antibodies and one Fc-fusion protein were evaluated during the pH jump thaw process and similar effects were observed. The results provide a new tool to study the kinetics of therapeutic protein aggregation upon pH increase. Keywords: Monoclonal antibodies, Freeze-thaw, Protein aggregation, Protein stability